Parathyroid ectopia: development of a surgical algorithm based on operative findings. Issue 11 (9th September 2015) - Gunasekaran, S; Wallace, H; Snowden, C; Mikl, D; England, R J A
Abstract: Objectives: To study the incidence of ectopic parathyroid adenomata from a single surgical series, and to devise a surgical algorithm from the results to follow when an adenoma cannot initially be located. Methods: A retrospective review was conducted of prospectively collected data. The study comprised all patients who underwent parathyroidectomy between June 2001 and February 2008 under the care of the senior author. A systematic surgical protocol was developed for locating ectopic superior and inferior parathyroid adenomata based on the order of incidence identified from the database. Results: Parathyroid ectopia occurs in approximately 10 per cent of hyperparathyroidism cases. It is more common in superior than inferior parathyroid glands. The most common superior location is the right retroesophageal position and the most common inferior location is within the left thymic remnant. Conclusion: Prospective data collection and subsequent analysis can be used to develop a systematic surgical protocol to aid the localisation of ectopic enlarged parathyroid glands in the surgical management of hyperparathyroidism.